Pediatric pelvic pyomyositis: initial MRI can be misleading. Issue 6 (November 2016) - Chotai, Pranit N.; Hsiao, Mark S.; Pathak, Indu; Banh, Diem; Abdou, Marwa; Abdelgawad, Amr A.
Abstract : Pelvic pyomyositis is an infection of the skeletal muscles around the hip joint. Fever, hip pain, limp, and leukocytosis are common; however, the clinical picture is often vague. MRI is the current gold-standard imaging for pyomyositis. No studies in the current literature have reported an unremarkable initial MRI in a patient with symptomatic pyomyositis. An adolescent female presented with symptomatic pelvic pyomyositis, but admission MRI was normal. A follow-up MRI indicated development of pelvic pyomyositis. The patient was successfully managed nonoperatively. The initial MRI in pyomyositis can be misleading. Patients should be admitted and MRI should be repeated, as indicated clinically.